Korean Medical Treatment Including Miniscalpel Acupuncture for Patients After Rotator Cuff Tear Surgery: A Report of Two Cases - Su Gyeong Kim; Eun Jin Park; Jae Eun Lim; Hyun Jeong Do; Jeong Yoon Kim; Sung Woo Cho; Hyun Min Yoon; Cheol Hong Kim (MEDrang Inc., 2019)
This study aimed to report the effect of Korean medical treatment including miniscalpel acupuncture on 2 patients who underwen tsurgery for rotator cuff tear. They were treated for almost 4 weeks at the Department of Acupuncture and Moxibustion, Dong-Eui University Korean Medicine Hospital. Visual analog scale (VAS), and range of movement (ROM) were used to evaluate treatment effects. In both patients, shoulder pain and restriction of shoulder joint movement improved after miniscalpel acupuncture treatment. In Case 1, shoulder pain decreased from a VAS score 8 to a VAS score 3, and ROM of the shoulder improved from flexion 100° to 160°, extension 10° to 30°, abduction 90° to 130°, adduction 10° to 40°, internal rotation 10° to 50°, and external rotation 10° to 50°. In Case 2, shoulder pain, which was rated a VAS score 8 at first-visit, disappeared, and ROM of the shoulder recovered to normal range. These results suggest miniscalpel acupuncture may contribute to the recovery process after rotator cuff tear surgery.